Fostering community resilience homeland security and Hurricane Katrina - Lansford, Tom (Homeland security, 2010)
Using the Mississippi Gulf Coast as a case study, this book focuses on the aftermath of Hurricane Katrina and develops the concept of resilience and how it applies to Homeland Security in the aftermath of the worst natural disaster to hit the United States.